In vitro gastrointestinal-resistant pectin hydrogel particles for β-glucuronidase adsorption. Issue 3 (11th February 2017) - Popov, Sergey V.; Markov, Pavel A.; Patova, Olga A.; Vityazev, Fedor V.; Bakutova, Larisa A.; Borisenkov, Mikhail F.; Martinson, Ekaterina A.; Ananchenko, Boris A.; Durnev, Eugene A.; Burkov, Andrey A.; Litvinets, Sergey G.; Belyi, Vladimir A.; et al.
Abstract: Pectin hydrogel particles (PHPs) were prepared by ionotropic gelation of low methylesterified pectin of Tanacetum vulgare L. with calcium ions. Wet PHPs prepared from TVF exhibited a smaller diameter and the lower weight as well as exhibited the best textural properties in terms of hardness and elasticity compared to the PHPs prepared from commercial low methylesterified pectin (CU701) used for comparison. Upon air drying, PHPs prepared from CU701 became small and dense microspheres whereas the dry PHPs prepared from TVF exhibited a drop-like shape. The morphology of dry PHPs determined by scanning electron microscopy revealed that the surface of the TVF beads exhibited fibred structures, whereas the PHPs prepared from CU701 exhibited a smooth surface. The characterization of surface roughness using atomic force microscopy indicated less roughness profile of the PHPs prepared from TVF than CU701. PHPs prepared from TVF were found to possess in vitro resistance to successive incubations in simulated gastric (SGF), intestinal (SIF), and colonic fluid (SCF) at 37 °C for 2, 4 and 18 h, respectively. The PHPs prepared from CU701 swelled in SGF and then lost their spherical shape and were fully disintegrated after 4 h of incubation in SIF. The PHPs from TVF, which were subjected to treatment with SGF, SIF and SCF, were found to adsorb microbial β -glucuronidase ( β G) in vitro . The data obtained offered the prospect for the development of the PHPs from TVF as sorbents of colonic β G for the inhibition of re-absorption of estrogens.